In vitro antibacterial activity of Averrhoa bilimbi L. leaves and fruits extracts - Zakaria, Zainul Amiruddin; H, Zaiton; Henie, E. F. P.; Mat Jais, Abdul Manan; E. Zainudin, Engku Nuraishah Huda (Medwell Journals, 2007)
The present study was carried out to determine the in vitro antibacterial activity of aqueous and chloroform extracts of the leaves and fruits of Averrhoa bilimbi L. using the standard disc diffusion test. The air-dried leaves and fruits of A. bilimbi were separately soaked in distilled water or chloroform (1:10; wv-1) for 24 h and the resultant supernatants were filtered. The aqueous extract was freeze-dried while the chloroform extract was evaporated to dryness under reduce pressure to obtained the crude dried extracts, which were prepared in the concentration of 25, 50 and 100 mg mL 1 prior to the antibacterial assay. The results obtained demonstrated the potential of A. bilimbi extracts against some of the Gram-positive and-negative bacteria. The 100 mg mL 1 aqueous extract of A. bilimbi’s leaves and fruits showed positive antibacterial activity against the Gram-positive S. aureus, S. epidermis B. cereus, C. diphteriae with the latter also gave positive effect against K. rhizophila. Both extracts also exhibited positive antibacterial activity against the Gram-negative S. typhi, C. fuendii and A. hydrophila. On the other hand, the 100 mg mL 1 chloroform extracts of A. bilimbi’s leaves and fruits demonstrated antibacterial activity against the Gram-positive S. aureus, S. epidermis, B. cereus, K. rhizophila and C. diphteriae and Gram-negative S. typhi, C. fuendii, A. hydrophila and P. vulgaris. In conclusion, the A. bilimbi leaves and fruits possess potential antibacterial activity that requires thorough study.